1996
DOI: 10.1007/bf02506794
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the transition to high school on the self‐system and perceived social context of poor urban youth

Abstract: Examined the effects of the normative school transition to senior high school (n = 330) on the self-system and perceived school and peer social contexts of poor, black (n = 83), European American (n = 115), Latino (n = 105), and Asian American (n = 27) youth in the public school systems of three Eastern urban cities. The only negative effect of the school transition on the self-system was a decline in grade point average (GPA). Concurrently, the school transition was perceived to be associated with changes in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
102
1
2

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(110 citation statements)
references
References 33 publications
5
102
1
2
Order By: Relevance
“…This study's findings therefore suggest that support perceptions are fixed neither in persons nor in time. Although previous researchers have investigated associations between changes in school environments and changes in psychological and academic functioning, they have generally focused on linear patterns attributable to other broader changes such as school transitions and developmental shifts (Eccles, Wigfield, Midgley, & Reuman, 1993;Reddy, Rhodes & Mulhall, 2003;Seidman, Aber, Allen, & French, 1996). The findings from this study highlight the need for dynamic approaches to studying students' adaptation over time.…”
Section: Discussionmentioning
confidence: 86%
“…This study's findings therefore suggest that support perceptions are fixed neither in persons nor in time. Although previous researchers have investigated associations between changes in school environments and changes in psychological and academic functioning, they have generally focused on linear patterns attributable to other broader changes such as school transitions and developmental shifts (Eccles, Wigfield, Midgley, & Reuman, 1993;Reddy, Rhodes & Mulhall, 2003;Seidman, Aber, Allen, & French, 1996). The findings from this study highlight the need for dynamic approaches to studying students' adaptation over time.…”
Section: Discussionmentioning
confidence: 86%
“…More vulnerable adolescents, those with fewer sources of social support, and those moving into more impersonal schools may be relatively more susceptible to the adverse consequences of changing schools. Poor inner-city youngsters appear to be especially likely to show transition-related negative decrements in self-esteem, achievement, classroom preparation, perceptions of the school environment, reports of social support, and participation in extracurricular activities (Eccles, 2004;Seidman, Aber, Allen, & French, 1996;Seidman, Allen, Aber, Mitchell, & Feinman, 1994). Interpersonal relationships play a role, as well.…”
Section: Schoolsmentioning
confidence: 99%
“…After the high school transition, students tend to have lower GPAs and attendance, and higher levels of negative interactions with peers [5,6]. Seidman et al found that, in comparison to the transition to middle school, students transitioning to high school perceived less support from and less involvement with school [6].…”
Section: Introductionmentioning
confidence: 99%